Induksi Umbi Mikro Tanaman Daun Dewa (Gynura pseudochina (Lour.) DC) Secara In Vitro dengan Perlakuan Sukrosa dan Daminozide - Donny Hartanto; Sandra Ariﬁn Aziz; Diny Dinarti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
<!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The effects of sucrose and daminozide on in-vitro microtuber formation were evaluated for producing microtubers to supply year round microtubers and to facilitate sterilized explants exchange regionally and internationally. Uninodal stem segment explants were cultured on agar solidiﬁ ed Murashige and Skoog medium supplemented with 3% sucrose, 0.5 mg L-16-benzylaminopurine (BAP), 0.1 mg L-1 α-naphthaleneacetic acid (NAA) for bud multiplication for 3 months. Three nodals stem segment which already formed three perfect leaves were cultured on agar solidiﬁ ed MS medium, 3% sucrose and 1 mg L-1 NAA for two weeks to induce root formation (until ± minimum 60% of the explants rooted). The next step was the induction of three nodal stem segments for microtuber formation on agar solidiﬁ ed MS medium supplemented with 5 mg L-1 BAP and two levels of sucrose, four concentrations of daminozide for 10 weeks. Sucrose at 6% resulted in the signiﬁ cantly highest number of microtuber. The daminozide 41.29 mg L-1 stimulated tuberization at base of the stems and reduce number of microtuber formation in stolon. Keywords: daminozide, Gynura pseudochina (L.) DC, in vitro, microtuber, sucrose